An improvement in visual acuity accompanied by the development of RPE tear: a case report - Xinyu Liu; Shulin Liu; Zhiyan Xu; Youxin Chen (BMC Ophthalmology)
Abstract Background Retinal pigment epithelium (RPE) tear is a well-known complication of RPE detachment and is typically associated with significant visual acuity decline. However, in this case, despite the occurrence of an RPE tear there was an unexpected improvement in visual acuity. Case presentation A 68-year-old male presented with blurred vision in his right eye of a month’s duration. Pachychoroid neovasculopathy was diagnosed. After monthly anti-vascular endothelial growth factor injections over a three months period. the choroidal neovascular membrane gradually diminished. While the pigment epithelial detachment expanded and the subretinal fluid increased. This was accompanied by deterioration in the visual acuity of the patient. The anti-VEGF treatment was discontinued, expectant management was adopted. Three months later, a retinal pigment epithelium tear was observed near the fovea, unexpectedly accompanied by complete resolution of the subretinal fluid, partial reattachment of the RPE detachment, and a significant improvement in visual acuity. Conclusions This case presents a rare instance of significant improvement in visual acuity and anatomical reconstruction of macular structure following the development of a retinal pigment epithelial (RPE) tear in a patient with pachychoroid neovasculopathy. We suggest that the fovea-sparing nature of the RPE tear in our case and the resulting “incision and drainage” effect may explain this unexpected outcome.